Glacial-interglacial flux and size variability of Fragilariopsis kerguelensis and Thalassiosira lentiginosa from the Indian sector of the Southern Ocean - Nair, Abhilash; Ghadi, Pooja; Mohan, Rahul; Manoj, M.C.; Crosta, Xavier; Shukla, Sunil; Thamban, Meloth (Deep Sea Research Part II: Topical Studies in Oceanography, 2020)
International audience